Generation and Characterization of a Virulent Leptosphaeria maculans Isolate Carrying a Mutated AvrLm7 Gene Using the CRISPR/Cas9 System - Zou, Zhongwei; Liu, Fei; Selin, Carrie; Fernando, W. G. Dilantha (Frontiers in Microbiology, 2020)
Blackleg, caused by the fungal pathogen Leptosphaeria maculans, is the most important disease affecting canola (Brassica napus) crops worldwide. We employed the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated (Cas) system to generate the mutant isolate umavr7 from a point mutation of the AvrLm7 coding region in a L. maculans isolate (UMAvr7). Reverse transcription PCR and unpublished transcriptome data confirmed that the AvrLm7 gene was knocked out in the mutant isolate. Pathogenicity tests indicated that umavr7 can cause large lesions on a set of B. napus differential lines that express different resistance (R) genes. Comparative pathogenicity tests between UMAvr7 (wild type) and umavr7 on the corresponding B. napus cultivar 01-23-2-1 (with Rlm7) showed that umavr7 is a mutant isolate, producing large grey/green lesions on cotyledons. The pathogenicity of the mutant isolate was shifted from avirulent to virulent on the B. napus Rlm7 line. Therefore, this mutant is virulence on the identified resistant genes to blackleg disease in B. napus varieties/lines. Superoxide accumulated differently in cotyledons in response to infection with UMAvr7 and umavr7, especially in resistant cultivar 01-23-2-1. Resistance/susceptibility was further evaluated on 123 B. napus genotypes with the mutant isolate, umavr7. Only 6 of the 123 genotypes showed resistance to umavr7. The identification of these six resistant B. napus genotypes will lead to further studies on the development of blackleg disease resistance through breeding and the identification of novel R genes.